Survey of mosquitoes species in Henda Village, Pulang Pisau District, Central Kalimantan, Indonesia in filariasis case area - INDRIA AUGUSTINA; M. YUSUF ILHAM KURNIAWAN; NOPTA TRIAWAN; MUHAMMAD FACHRIZAL MANTA; NATHASYA RIZKYANA RIYADI; MUHAMMAD ANDREAN SYAHRIDHO; ARINI RATNASARI; MILA KARMILA; ARIF RAHMAN JABAL (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Augustina I, Kurniawan MYI, Triawan N, Manta MF, Riyadi NR, Syahridho MA, Ratnasari A, Karmila M, Jabal AR. 2024. Survey of mosquitoes species in Henda Village, Pulang Pisau District, Central Kalimantan, Indonesia in filariasis case area. Biodiversitas 25: 4886-4893. Filariasis is a zoonotic disease found in tropical regions. One of the filariasis endemic areas is Henda Village, Pulang Pisau District, Central Kalimantan Province, Indonesia. Three cases of filariasis cases were identified in Henda Village. This study aimed to identify mosquito species that act as vectors in Henda Village. Mosquito samples were collected using human landing collection, resting collection, animal-baited traps, animal barrier screens, and light traps. A total of 650 mosquitoes were collected, including Culex quinquefasciatus (n=361), Mansonia bonneae (n=134), Mansonia uniformis (n=90), Aedes aegypti (n=46), Aedes albopictus (n=13), Coquillettidia crassipes (n=5), and Anopheles barbirostris (n=1). The human landing collection method caught the highest number of mosquitoes at 438 mosquitoes. Overall, the total number of mosquitoes obtained, the highest number of mosquitoes obtained was the species of Culex sp. was Cx. quinquefasciatus.